On the Highways of Literature: Herbert Croft’s Unfinished Business - Keen, Paul (Romanticism and Victorianism on the Net, 2008)
AbstractThis essay explores the ways that Herbert Croft’s ultimately unsuccessful literary career epitomized the late eighteenth-century world of struggling authors, pursuing their fortune along whatever paths seemed to be the most promising or, failing that, most available, across a far broader range of genres than we normally acknowledge in our accounts of professional authorship in this period. It explores Croft’s failed plans to produce what the Gentleman’s Magazine called the “Oxford Dictionary of the English Language,” but also on his considerable efforts to promote this and other literary projects. The second half of the essay focuses on Croft’s Letter to the Right Honourable William Pitt, which was printed in early March, 1788, at the end of a trip to London, and which was intended to generate support for his dictionary project. If the Letter to Pitt was remarkable for the dexterity with which Croft aligned his argument for the importance of a particular form literary professionalism with a set of related assumptions about the connections between public virtue and the national good, its many tensions foregrounded some of the paradoxes that were implicit in this process. Like many of the newspaper ads for his other works, the Letter to Pitt offers a compelling example of the extent to which Croft’s promotional efforts resulted in more intriguing literary texts than the works they were intended to promote.